Self-Determination Theory in Arabic Learning Strategies for Speaking at Pesantren Mambaus Sholihin - Mohammad Makinuddin; Friendis Syani Amrulloh (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study analyzes the learning strategy of Arabic speaking skills at the pesantren Mambaus Sholihin Gresik through the lens of Self-Determination Theory (SDT), identifying how peer tutors support relatedness, daily dialogue builds competence, interactive muhadathah facilitates autonomy, and a strict language environment inhibits psychological needs. Using a phenomenological approach with 12 purposive informants (2 Arabic teachers, 2 managers, 8 students), data collected through in-depth interviews, participatory observation (15 sessions), and documentation, analyzed with SDT-based phenomenological reduction. The findings show that optimal peer tutors meet relatability (reduction of language anxiety), daily dialogue develops competence through mastery experiences, while interactive sessions increase autonomy. A tight pedagogical environment cultivates controlled motivation, thereby inducing speech anxiety and consequent avoidance behavior in extramural contexts. The research produced a Hybrid Autonomy-Supportive Environment Model replacing punishment with Arab Challenge Reward, progressive scaffolding, peer autonomy networking, and the theme of student choice is more impactful for sustainable speaking competence. This model revolutionized Arabic language pedagogy from the practice of a repressive language environment to an SDT-based strategy, optimal for the motivation and fluency of students in the digital era.